2015
DOI: 10.1093/ckj/sfv089
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonasexit-site infection: treatment outcomes with topical gentamicin in addition to systemic antibiotics

Abstract: BackgroundAlthough, Pseudomonas exit-site infection (ESI) is recognized as a major complication of peritoneal dialysis (PD) with high risk of catheter loss due to refractory/recurrent infection or peritonitis, there is remarkably little literature about treatment outcomes. International Society for Peritoneal Dialysis guidelines advise the use of one to two antibiotics; in addition, we change standard exit-site care by stopping prophylactic mupirocin and starting regular use of gentamicin 1% cream.MethodsRetro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 10 publications
0
25
0
1
Order By: Relevance
“…As the number of patients with Pseudomonas peritonitis in current study was small, this remains an interesting observation and may be an area of future research. The superiority of either exit-site mupirocin or gentamicin in preventing PD peritonitis remains the subject of further investigation even though there are more evidence showing exit-site gentamicin to be associated with lower overall peritonitis rate [23,24].…”
Section: Peritonitis and Microbiologymentioning
confidence: 99%
“…As the number of patients with Pseudomonas peritonitis in current study was small, this remains an interesting observation and may be an area of future research. The superiority of either exit-site mupirocin or gentamicin in preventing PD peritonitis remains the subject of further investigation even though there are more evidence showing exit-site gentamicin to be associated with lower overall peritonitis rate [23,24].…”
Section: Peritonitis and Microbiologymentioning
confidence: 99%
“…Our analysis suggests that subcutaneous gentamicin injection around the cuff can be an important option in the treatment of PD patients with resistant ESI. The overall cure rate of 85% in our population was better than previously reported cure rates with different treatment methods 22–24. Therefore, subcutaneous gentamicin injection around the cuff is feasible for eradicating resistant ESI, as evidenced by the low incidence of recurrence of ESI after the procedure.…”
Section: Discussionmentioning
confidence: 45%
“…Bernardini et al showed that the daily application of the gentamicin cream to the exit site was effective in preventing the development of ESI by both gram-positive and gram-negative organisms 27. But the topical gentamicin cream did not show similar success rates in the treatment of pseudomonas ESI in Burkhalter et al’s study and the success rate of this treatment is not higher than 50%–60% 24. The biofilm formed by bacteria lowers the efficacy of the topical gentamicin in the treatment of ESI and systemic antibiotics cannot probably reach sufficient concentrations in the pericatheteral area in PD patients with ESI.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, found that E.coli was the most frequent Gram negative agent 12(23.5%), followed by P. aeruginosa 9(17.6%),while, P. aeruginosa was the most frequent Gram negative agent (8% -12%), followed by other Enterobacteriaceae (7% -14%).Felix et al (2015) found that, Pseudomonas ESI in PD patients from 135 patient presented in low range of 14(10.3%) (21). Chia et al (2014), found that Acinetobacter baumannii after 2000, was 9 (64%)was the most common species identified from the effluent, and the leading causes of infection were sterility break and GI microflora translocation (33).…”
Section: Antibiotic Sensitivitymentioning
confidence: 98%